Strategies for Diagnosis and Prevention of Venous Thromboembolism during Pregnancy - Shalini Jain Bagaria; V. B. Bagaria (Hindawi Limited, 2011)
Pregnancy and the postpartum period have an increased incidence of venous thromboembolism (VTE). The condition is unique during this period for several reasons. Primarily, because there is complexity in diagnosing this condition in view of altered physiology and preexisting edema in pregnancy and also because there are restrictions on the use of certain drugs and a need for vigilant monitoring of anticoagulant activities of drugs during the period. The problem is compounded and assumes the highest order of significance since two lives are involved and all the investigations and management done should also take into account the potential adverse effects on the foetus. In order to prevent the development of VTE during pregnancy, sound clinical evaluation for risk factors, risk stratification, and optimal use of resource both mechanical and pharmacological is necessary. This paper details strategies in preventing development of deep vein thrombosis and treatment of VTEs.